Giving back: women's entrepreneurial philanthropy - Oppedisano, Jeannette (Women in Management Review, 2004)
Traditionally, the concept of entrepreneurship included a for-profit bottom line. Recently, however, researchers have begun to explore an adaptation of this model called “social entrepreneurship”; that is, creating organizations for the greater good of a community, region, nation, or the world. These entrepreneurs use money that they made or inherited to establish organizations from a missionary and visionary posture. This is an arena where women have had significant impact, yet little has been written to celebrate their contributions. The purpose of this paper is to explore the concept of such philanthropy, to suggest where this social ethic might have had its origins, and to provide samples of women who have been entrepreneurial in their social commitment. Suggestions for future research on women's entrepreneurial philanthropy will also be made. © 2004, Emerald Group Publishing Limited
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-771-605-085-74X tex.type: [object Object]
Keywords: Entrepreneurialism; Philanthropy; Social action; United States of America; Women; dept.mgt

Historical Encyclopedia of American Women Entrepreneurs: 1776 to the Present - Oppedisano, Jeannette M. (Greenwood Press, 2000)
Keywords: Biography; Businesspeople; Biography; Businesswomen; Businesswomen; Encyclopedias; Encyclopedias; Businesspeople; History; United States; dept.mgt; faculty_collection

Role modeling as a pedagogical strategy in entrepreneurship education for women and girls: An interactive model of transformational learning - Oppedisano, Jeannette; Laird, Kenneth R (New England Journal of Entrepreneurship, 2006)
This article presents a pedagogical model that utilizes students as primary researchers in the identification, interviewing, and then reporting on women entrepreneurs as a major component of a multidisciplinary entrepreneurship course. The purpose of the course is to attract students who may not be familiar with the entrepreneurship concept itself, the role of women in such economic ventures, or the possibilities for people like themselves in such a career avenue. Students are exposed to the accomplishments of women entrepreneurs throughout U.S. history in the broad categories of agriculture and mining; construction; communication; manufacturing; service (both for profit and not-for-profit); transportation; and wholesale and retail trade. This content experience is then enhanced by the studentsʼ own direct interaction with and interviewing of women entrepreneurs. The implementation, potential outcomes, and possible adaptations of the course are described, and this transformational learning process model is illustrated. © Published by DigitalCommons©SHU, 2006.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-478-351-659-477 tex.type: [object Object]
Keywords: dept.mgt

Leadership theory and practice: a “case” in point - Armandi, Barry; Oppedisano, Jeannette; Sherman, Herbert (Management Decision, 2003)
Leadership theory has little value if it cannot be applied to real world situations. A summary review of the literature on leadership theory is provided here first. A disguised real case concerning Ted Shade, a Vice-President at Galactic Chips, Inc. is then provided which describes a manager who is extremely task-oriented. The case analysis follows. It includes questions and answers which connect leadership theory to case specifics and requires learners to analyze the case using differing leadership models. © 2003, MCB UP Limited
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-531-695-412-316 tex.type: [object Object]
Keywords: Leaders; Leadership; Management styles; Psychology; dept.mgt